The influence of capital adequacy ratio (car) and loan to deposit ratio (ldr) on return on assets (roa) in banking companies listed on the indonesia stock exchange - Dwi Purwaningrum; Asep Daman; Dany Arya Putra; Erwin Kurniawan; , Dapa Ari Saputra (Institute of Computer Science (IOCS), 2026)
The objective of this research is to analyze how Capital Adequacy Ratio and Loan to Deposit Ratio affect Return on Assets in Indonesian banks listed on IDX from 2021 to 2025. Previous studies show inconsistent findings regarding the effect of CAR and LDR on ROA. Some found a positive effect, while others found negative or insignificant results. This inconsistency indicates a research gap that needs further testing in the post-pandemic period. The population includes all banks listed on IDX in 2025. The sample was selected using purposive sampling: banks listed consecutively from 2021-2025 with complete annual reports. Based on these criteria, 16 banks were selected. This study uses a panel data design with 80 observational data to capture cross-sectional and time-series effects. Multiple linear regression with SPSS was used. Classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation were conducted prior to analysis. The results show that CAR and LDR negatively affect ROA. Specifically, CAR has a negative and significant effect with B = -0.149, Beta = -0.303, t = -2.881, p = 0.005. LDR also has a negative and significant effect with B = -0.164, Beta = -0.249, t = -2.370, p = 0.020. Simultaneously, CAR and LDR significantly affect ROA with F = 6.739, p = 0.002. CAR and LDR explain 14.9% of ROA variation, with Adjusted R² = 0.149. The novelty of this study is its use of recent data from 2021-2025 during economic recovery. The implication is that banks should optimize CAR and LDR levels to maintain profitability